Penyelesaian Sengketa Pekerja dalam Perjanjian Kerja melalui Pengadilan Hubungan Industrial - Satriawan, Deki (Faculty of Law, University of Dr. Soetomo, 2023)
The number of Indonesian citizens who are adults and have reached a productive working life is not commensurate with the existing and available jobs. Most of the workforce in Indonesia has low education, this causes their bargaining position in obtaining work to be low. Work is the main source of income for livelihood, survival and life of all people. Obtaining a job and earning a good and decent income is the basic right of every human being. The Indonesian government has created legislation regarding employment to regulate the relationship between workers and employers. However, there are still many violations committed by employers in making work agreements. The reason is because the position of workers is weak due to the lack of available jobs. So that when looking for work, workers are willing to enter into a work agreement, without paying attention to the rights they lose when entering into a work agreement. Settlement of employment disputes between workers and employers regarding work agreements can be resolved in the industrial relations court. Legal protection for workers in employment agreements is necessary due to their weak position.